Provenance Study and Tectonic Implications on Rock Sequences in The Lengguru Fold Belt of Western Papua: Constraints from Zircon Fission Track Thermochronology - Edy Sutriyono (Forum Teknik, 2003)
The present zircon fission track thermochronologt study reveals Triassic to Pliocene source terrains supplying clastic materials into the present successions in western Papua. The provenance of sedimentary rocks in the region appears to have associated with igneous activities, suggesting an episode of tectonic events in Mesozoic and Cenozoic. Importantly, the Pliocene Buru Formation in the Lengguru Fold Belt contains abundant Paleogene volcanic zircons, which might have been derived from erosion of the Weylond Terrane in the latest Miocene-Pliocene. This suggests the Weyland Terrane was part of the Paleogene 'Caroline Arc, that was eroded after Lute Miocene collision with the western Papua microcontinent. The main compressional pulse in the studied area occurred from -12-4 Ma. The deformation in the mountainous belt in western Papua from 4-0 Ma has been dominated by transpression. This transpressional regime continued in the fold belt, but with less convergence. Meanwhile, compression continued in the frontal part of the Lengguru Fold Belt, creating Pleistocene foldingfeatures such as the Buru Anticline, the Umar Anticline, and the Poronggo Anticline in the eastern Lengguru Fold Belt section. At the present day, transpression is occurring along theTarera'Aiduna Fault with ongoing uplift of the western Papua Fold Belt. However, extension and subsidence are occurring in the Lengguru Fold Belt southeast of Cendrawasih Bay.Keywords : sedimentary rocks, zircon fission, transpression